2016
DOI: 10.1007/s13181-016-0556-6
|View full text |Cite|
|
Sign up to set email alerts
|

Baclofen Toxicity Causing Acute, Reversible Dyskinesia

Abstract: The following unique case demonstrates an episode of acute dyskinesia secondary to oral baclofen toxicity. We discuss an 80-year-old man with a history of Stage III chronic kidney disease, coronary artery disease, diabetes and stroke who presented to the Emergency Department with new onset of behavioral changes and irregular jerking movements. The patient had been recently prescribed baclofen 10mg twice daily for a back strain he suffered; he subsequently was admitted to the hospital, and his symptoms resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Some rodent models have shown that GABA receptors are expressed on both dopaminergic and GABAergic neurons [7]. Therefore, exposure to baclofen may cause activation of GABA receptors and inhibit the release of both GABAergic and dopaminergic neuron activity, modifying the release of both GABA and dopamine [7]. So hence we theorize that in our case, a combination of baclofen and clozapine resulted in enhanced, diminished dopaminergic activity.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Some rodent models have shown that GABA receptors are expressed on both dopaminergic and GABAergic neurons [7]. Therefore, exposure to baclofen may cause activation of GABA receptors and inhibit the release of both GABAergic and dopaminergic neuron activity, modifying the release of both GABA and dopamine [7]. So hence we theorize that in our case, a combination of baclofen and clozapine resulted in enhanced, diminished dopaminergic activity.…”
Section: Discussionmentioning
confidence: 68%
“…Our patient has been taking baclofen and clozapine for his neuropathic pain and physiologic tremor, respectively, for the last 30 years. Baclofen, a muscle relaxant, acts as a GABA receptor agonist, decreasing excitatory neurotransmitter release from presynaptic terminals [7]. It is the drug of choice in treating multiple sclerosis, spinal cord injuries, and other musculoskeletal disorders [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The video for the baclofen dyskinesia case [1] is here. We apologize the video link was not included in our December 2016 issue.…”
mentioning
confidence: 99%